SAFETY AND CONFIDENTIALITY OF PATIENT DATA IN ELECTRONIC MEDICAL RECORD SYSTEMS - Reliana Cristiana de Jesus; Aulia Nur’aini; Adeleo Ariko Verdiansyah; Amalia Fajriyatun Sholihah; Renata de Araujo; Ahmad Sunandar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of information technology has brought great changes in health services, one of which is through the implementation of the Electronic Medical Record System (RME). The use of RME provides various advantages, such as ease of information access, increased service efficiency, and reduced use of paper-based documents. However, behind these benefits there are challenges related to the security and confidentiality of patient data. Health data is private and very sensitive information so it requires maximum protection from various threats, such as data leakage, unauthorized access, data manipulation, and cyber attacks. This article aims to examine the importance of the security and confidentiality of patient data in the electronic medical record system, identify threats that can occur, and explain various efforts that can be made to maintain the security of health information. This research uses the literature study method by analyzing various national and international journals, books, and regulations that apply in Indonesia. The results of the study show that the implementation of information security technology combined with compliance with regulations and improving human resource competence is the main factor in maintaining the confidentiality of patient data.